TARJIMADA QO'LLANILADIGAN AN'ANAVIY HAMDA INNOVATSION USULLAR («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article analyzes the traditional and innovative methods used in translation.As a research methodology, methods of literature analysis and comparative analysis were used.The results of the study show that the use of innovative technologies in the translation process, along with traditional methods, serves to improve the quality and efficiency of translation. The conclusion section emphasizes the need to harmonize traditional and modern translation methods.
Keywords: translation, traditional methods, innovative methods, translation technologies, translation quality